(untitled) (Horizontes de Enfermería, 2021)
In order to establish the relationship between bovine brucellosis, human brucellosis and the risk factors, under the scheme of “one health”, a study was carried out in 10 Agricultural Productive Units (APUs) in the province of Carchi, where 50 people and 450 cattle were interceded. To identify the risk factors, a questionnaire was developed and applied through an interview. The animal diagnosis was made using Polarized Fluorescence tests in milk, Rose Bengal in blood serum, and positive samples confirmed by competitive ELISA, using the same diagnostic scheme for human brucellosis in blood serum. The relationship between bovine brucellosis and human brucellosis was determined using the Kappa index. Epidemiological case-control studies identified the associated risk factors through Odds ratios. The results show 5 APUs diagnosed as positive for bovine brucellosis, of which three were diagnosed positive for human brucellosis. The concordance analysis between bovine and human brucellosis shows a Kappa index of 0.6 (0.104 - 1.096 95% CI), denoting a moderate qualitative concordance. The following risk factors were identified for human brucellosis: the consumption of raw or unpasteurized milk, the absence of personal protective equipment (PPE), accidents with used sharp-pointed materials, the presence of different animal species, and the presence of positive reactive animals, whereas, the exclusive use of a site designed for births, and the suitable elimination of biological waste constituted protection factors.